Obesity and inflammatory biomarkers in women with polycystic ovary syndrome. (September 2015) - Shen, Szu-Hung; Shen, Szu-Yu; Liou, Tsan-Hon; Hsu, Ming-I; Chang, Yuan-chin Ivan; Cheng, Chih-Yu; Hsu, Chun-Sen; Tzeng, Chii-Ruey
Abstract: Objective: To evaluate the roles of obesity and inflammatory biomarkers associated with medical complications in women with PCOS. Study design: Retrospective, BMI-matched study. A total of 330 patients, including 165 women with PCOS and 165 women without PCOS, were evaluated. The insulin resistance (homeostasis model assessment insulin resistance index – HOMA) and lipid profiles were assessed. The adiponectin, leptin, ghrelin, resistin, anti-müllerian hormone (AMH), sex hormone-binding globulin (SHBG), high sensitivity C-reactive protein (hs-CRP), and interleukin-6 (IL-6) levels were also measured. Results: Women with PCOS had significantly higher AMH, fasting insulin, total cholesterol, and low-density lipoprotein levels and lower SHBG levels compared with the controls. There was no difference in the serum obesity and inflammatory biomarkers between the PCOS cases and the controls. After adjusting for BMI and age, IL-6 was positively correlated with HOMA, and SHBG was negatively correlated with HOMA, triglyceride, and LDL. Conclusions: The serum adipokines levels are not good markers for PCOS. PCOS patients were characterized by their high AMH and low SHBG levels. A low level of SHBG should play an important role in the pathogenesis of the medical complications observed in women with PCOS. Clinical trial registration numberNCT01989039 .